Handbook of chemical processing equipment - Cheremisinoff, Nicholas P. (Boston : Butterworth-Heinemann, 2000)
Provides descriptions of the working principles, intended applications, selection criteria, and fundamental design principles for equipment used throughout the process and allied chemical industries.
Heat Exchange Equipment; Evaporative Cooling Equipment; Evaporating and Drying Equipment; Distillation Equipment; Mass Separation Equipment; Mechanical Separation Equipment; Mixing Equipment; Calculations for Select Operations; Index.
Includes bibliographical references and index.
Keywords: Chemical plants -- Equipment and supplies; Chemical plants -- Equipment and supplies -- Handbooks, manuals, etc; Chemical processes -- Equipment and supplies -- Handbooks, manuals, etc; Electronic books